MONITORING THE CRUST MOVEMENT AT THE SALTO CAXIAS HYDROELECTRIC POWER DAMS: An Analysis of the Stability of Supporting and Controlling Points - NASCIMENTO TEIXEIRA, NIEL; DAMASCENO FERREIRA, LUIZ DANILO (Boletim de Ciências Geodésicas, 2010)
The Electricity Company of Paraná State-Brazil has built several hydroelectric power dams along the Iguaçu River. The last one was Salto Caxias dam, a 67 concrete unit meter high with 131 square kilometers of flooded area corresponding to 3.6x109 m3 water volume. 87 points were established around the flooded area, aiming at monitoring the crust movement of the area. Due to the fact that most of the points are located near the reservoir, where deformations might happen, 13 points were located at the farthest possible position from the reservoir. They were used as reference points for monitoring the others. This work presents the methodology applied to the analysis of the stability of the reference points, the results and conclusions as well. Data set collected during two GPS campaigns were used to realize the investigation.